A Novel Piezoelectric Biosensor for Cholera Toxin Detection Based on Ganglioside GM1 Incorporated Supported Lipid Membrane and Biocatalyzed Deposition Amplification - Li, Yu; Wei, Zheng; Yu, Hongwei; Zhu, Jianhang; Wang, Yuansheng (Asian Journal of Chemistry, 2013)
A novel piezoelectric method for the detection of cholera toxin based on the supported lipid layer incorporated with ganglioside GM1 and the biocatalyzed deposition amplification has been developed. The planar supported lipid membrane was prepared as biosensing interface via spontaneous spread of ganglioside GM1-incorporated phospholipid vesicles on the octadecanethiol-coated gold surface. The specific interaction of multivalent cholera toxin by ganglioside GM1 molecules enables the biosensor to be implemented via a sandwiched format using anti cholera toxin antibody (CT antibody). After the "sandwich" immunoreaction, the horseradish peroxidase (HRP) labeled goat antirabbit IgG antibody (HRP-G-anti RIgG) was introduced into the detection cell to combine with the anti cholera toxin antibody on the sensor surface. The enzyme labeled HRP-G-anti RIgG act as a biocatalyst which could accelerate the oxidation of 4-chloro-1-naphthol by H2O2 to yield the insoluble product benzo-4-chlorohexadienone on the surface of quartz crystal microbalance, resulting in a mass increase that was reflected by a decrease in the resonance frequency of the quartz crystal microbalance. The proposed approach could allow for the determination of cholera toxin in the concentration range of 0.1-500.0 ng/mL. The interference experiment results demonstrated that the developed biosensor performed with highly resistance to nonspecific adsorption.